Establishing tall fescue using drip irrigation and protective covers - Bach, Alex Patrick (Kansas State University, 2021)
Subsurface drip irrigation (SDI) may save water but the effectiveness of SDI in establishing turfgrass from seed across different soil types and climates requires further investigation. Research is even more limited regarding the establishment of cool-season turfgrasses using turfgrass protective covers in combination with SDI. Two research projects were conducted at the Rocky Ford Turfgrass Research Center, Manhattan, KS. In both, turfgrass establishment was evaluated with measurements of turfgrass green cover (GC), visual turfgrass quality (TQ), and ground and drone-based normalized difference vegetation index (NDVI). The first project (Chapter 1) investigated effects of different frequencies and methods of irrigation, and two cultivation methods on the establishment of a cool-season turfgrass, tall fescue [Festuca arundinacea (Schreb.)], from seed in the fall of 2019 and 2020. Turfgrass established faster in SDI than the other methods including overhead sprinklers and an above-ground drip irrigation system. Overall, the best establishment among irrigation methods was with SDI that applied water 2x per day vs. 3x or 1x per day. Cultivation had no effect on establishment and no damage occurred to SDI buried at a depth of 15.24 cm when plots were core aerified with 7.62 cm hollow irrigation tines. The second study (Chapter 2) was repeated sequentially in the spring of 2020 and focused on the use of different irrigation methods in conjunction with protective turfgrass covers consisting of polyester mesh, a straw blanket, and no cover (control). Both cover types improved establishment compared to no cover, generally in the order of, from highest to lowest, polyester mesh > straw blanket > no cover in both trials. Establishment of tall fescue with SDI was similar to overhead irrigation and aboveground drip irrigation in the spring study. Soil temperature was ~7°C higher under polyester mesh turf covers than under straw blanket and in no cover plots. Polyester covers mitigated low temperature extremes, but both cover types prevented erosion early in the study, resulting in better establishment in covered plots, especially in polyester mesh plots. Overall, results demonstrated that SDI established tall fescue from seed similarly to or better than overhead sprinklers when applying 150% reference evapotranspiration 2x per day, and that covers improved spring establishment.
Keywords: Irrigation technology; Irrigation efficiency; Subsurface drip irrigation; Erosion control blankets; Cool season turfgrass